Resolvin D1 Alleviates Ventilator-Induced Lung Injury in Mice by Activating PPARγ/NF-κB Signaling Pathway. (4th June 2019) - Xia, Haifa; Wang, Jingxu; Sun, Shujun; Wang, Fuquan; Yang, Yiyi; Chen, Lin; Sun, Zhipeng; Yao, Shanglong
Abstract : As one of the basic treatment modalities in the intensive care unit (ICU), mechanical ventilation can cause or aggravate acute lung injury or ventilator-induced lung injury (VILI). Resolvin D1 (RvD1) is an endogenous polyunsaturated fatty acid derivative with strong anti-inflammatory action. In this study, we explored if RvD1 possesses a protective effect on VILI. Mice were ventilated with high tidal volume (40 mL/kg, H V T ) for 4 h and were then intraperitoneally administered RvD1 at the beginning of high tidal volume ventilation and given GW9662 (a PPAR- γ antagonist) intraperitoneally 30 min before ventilation. RvD1 attenuated VILI, as evidenced by improved oxygenation and reduced histological injury, compared withH V T -induced lung injury. Similarly, it could ameliorate neutrophil accumulation and production of proinflammatory cytokines in lung tissue. In contrast, the protective effect of RvD1 on lung tissue could be reversed by GW9662. RvD1 mitigated VILI by activating peroxisome proliferator-activated receptor gamma (PPAR- γ ) and inhibiting nuclear factor-kappa B (NF- κ B) signaling pathways in mice. In conclusion, RvD1 could reduce the inflammatory response in VILI by activating PPAR- γ and inhibiting NF- κ B signaling pathways.